A 330–500 GHz Zero-Biased Broadband Tripler Based on Terahertz Monolithic Integrated Circuits. (1st February 2015) - Ren, Tian-Hao; Zhang, Yong; Yan, Bo; Xu, Rui-Min; Yang, Cheng-Yue; Zhou, Jing-Tao; Jin, Zhi
Abstract A 330–500 GHz zero-biased broadband monolithic integrated tripler is reported. The measured results show that the maximum efficiency and the maximum output power are 2% and 194 μW at 348 GHz. The saturation characteristic test shows that the output 1 dB compression point is about −8.5 dBm at 334 GHz and the maximum efficiency is obtained at the point, which is slightly below the 1 dB compression point. Compared with the conventional hybrid integrated circuit, a major advantage of the monolithic integrated circuit is the significant improvement of reliability and consistency. In this work, a terahertz monolithic frequency multiplier at this band is designed and fabricated.